Study of the competitiveness of Polish foreign trade using the augmented Glejser, Goossens and van den Eede method - Salamaga, Marcin (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
This paper proposes a modified version of the Glejser, Goossens and van den Eede method of testing the intensity of intra-industry foreign trade (1982). The original method was not equipped with adequate statistical and econometric instrumentation, which markedly reduced its practical utility. The paper proposes a study of the dynamics, direction of change and co-integration of the time-series of the Glejser, Goossens and van den Eede indicators. This kind of test procedure has been used to study the competitiveness of Poland’s foreign trade in four groups of products of different levels of technological advancement. The findings show that the Polish economy has an increasing ability to sell goods with a slight technological advancement, whereas its competitiveness in high-tech goods is poor
Argumenta Oeconomica, 2018, Nr 1 (40), s. 167-180
Keywords: Glejser index; intra-industry trade; time series; cointegration